2017
DOI: 10.1002/cncr.30881
|View full text |Cite
|
Sign up to set email alerts
|

Stomach cancer survival in the United States by race and stage (2001‐2009): Findings from the CONCORD‐2 study

Abstract: BACKGROUND Stomach cancer was a leading cause of cancer-related deaths early in the 20th century and has steadily declined over the last century in the United States. Although incidence and death rates are now low, stomach cancer remains an important cause of morbidity and mortality in black, Asian and Pacific Islander, and American Indian/Alaska Native populations. METHODS Data from the CONCORD-2 study were used to analyze stomach cancer survival among males and females aged 15 to 99 years who were diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 193 publications
(116 citation statements)
references
References 39 publications
5
95
0
5
Order By: Relevance
“…A description of the data from the 37 participating cancer registries, and the rigorous and advanced statistical methods used to evaluate and analyze the data, are presented in an accompanying article by Allemani et al We focused on patients diagnosed during 2 calendar periods (2001‐2003 and 2004‐2009) because the method used by US cancer registries to collect and report anatomic stage (SEER Summary Stage 2000) changed beginning on January 1, 2004. We observed 5‐year survival to be high (≥80%) for breast cancer in women, prostate cancer, and acute lymphoblastic leukemia (ALL) in children; moderate (50%‐80%) for cancers of the colon, rectum, and cervix; and low (<50%) for cancers of the stomach, liver, lung, and ovary (Table ) . These observations are consistent with those of long‐term trends in survival in the United States for many leading cancers in both males and females and children .…”
Section: Introductionsupporting
confidence: 81%
“…A description of the data from the 37 participating cancer registries, and the rigorous and advanced statistical methods used to evaluate and analyze the data, are presented in an accompanying article by Allemani et al We focused on patients diagnosed during 2 calendar periods (2001‐2003 and 2004‐2009) because the method used by US cancer registries to collect and report anatomic stage (SEER Summary Stage 2000) changed beginning on January 1, 2004. We observed 5‐year survival to be high (≥80%) for breast cancer in women, prostate cancer, and acute lymphoblastic leukemia (ALL) in children; moderate (50%‐80%) for cancers of the colon, rectum, and cervix; and low (<50%) for cancers of the stomach, liver, lung, and ovary (Table ) . These observations are consistent with those of long‐term trends in survival in the United States for many leading cancers in both males and females and children .…”
Section: Introductionsupporting
confidence: 81%
“…We observed that age-standardized 5-year net survival for lung cancer (19.0%) was 4.2% higher than that for liver cancer (14.8%) 18 but lower than for the other cancers addressed in this Supplement, including stomach cancer (29.0%), 19 ovarian cancer (41.0%), 20 cervical cancer (62.8%), 21 rectal cancer (64.0%), 22 colon cancer (64.6%), 23 acute lymphoblastic leukemia in children (88.1%), 24 breast cancer (88.6%), 25 and prostate cancer (96.9%). 26 …”
Section: Discussionmentioning
confidence: 62%
“…If an age‐specific estimate could not be obtained, we merged data for adjacent age groups and assigned the combined estimate to both age groups. If 2 or more age‐specific estimates could not be obtained, we present only the pooled, unstandardized estimates for all ages combined: these estimates are italicized in Supporting Tables 2 and 3 in other articles of this supplement …”
Section: Methodsmentioning
confidence: 99%